Revisión documental de la autopsia psicológica y la adaptación de instrumentos psicométricos. (2020)
In the present work, it is intended to carry out a theoretical journey in front of a highly important subject for legal psychology, doubtful deaths and an instrument that is responsible for clarifying them through a psychological analysis of the victim, created from the reconstruction psychopathological post-death by means of important data provided by relatives, couples, friends or close companions to the deceased. The Psychological Autopsy is an instrument that is in charge of collecting data and information about a deceased person, to determine the veracity of his cause of death, which was initially proposed as doubtful. This type of instrument has been subject to a knowledge gap, therefore, in order to nourish this interesting field of research, a documentary review was carried out in this work, here the Integrated Psychological Autopsy Model (MAPI) is mentioned, which It is the most representative instrument within this theme. Finally, it is suggested for future investigations carried out on the subject, that an adaptation of this instrument be carried out for the Colombian military population, thus achieving the creation of a tool that will clarify the forensic opinion assigned to the death of a person in said scope, without neglecting the possibility of implementing it as a preventive method against suicide; thus obtaining a useful tool for this population.